A steady-state model for heat pipes of circular or rectangular cross-sections - Ismail, K. A R; Zanardi, M. A. [UNESP] (Elsevier, 1996)
The objective of this paper is to present a generalized analytical-numerical model of the internal flow in heat pipes. The model formulation is based on two-dimensional formulation of the energy and momentum equations in the vapour and liquid regions and also in the metallic tube. The numerical solution of the model is obtained by using the descretization scheme LOAD and the SIMPLE numerical code. The flow fields, as well as the pressure fields, for different geometries were obtained and discussed. Copyright © 1996 Elsevier Science Ltd.
Keywords: Circular heat pipe; Generalized model; Rectangular heat pipe; Two-dimensional model; Equations of motion; Mathematical models; Numerical methods; Pipe flow; Pressure drop; Temperature distribution; Heat pipes